In Silico Analysis Identifies Upregulated lncRNA DLGAP1-AS1 Which Is Correlated to Poor Prognosis and Promotes Cell Proliferation in Glioblastoma. (15th March 2022) - Huang, Yinxing; Liu, Li; Fang, Meng; Yan, Wangjun
Abstract : Long noncoding RNAs have been reported to regulate the tumorigenesis, growth, and metastasis of glioblastomas. In this study, we identified 1623 differently expressed mRNAs and 38 lncRNAs utilizing the CGGA and TCGA databases. Among these mRNAs and lncRNAs, we focused on DLGAP1-AS1 in this study. The results demonstrated that DLGAP1-AS1 was higher in WHO IV glioma than in WHO II and WHO III gliomas, higher in WHO III glioma than in WHO II glioma samples, higher in IDH1 wildtype glioma than in IDH1-mutant glioma samples, and higher in 1p/19q noncodeletion glioma than in 1p/19q codeletion glioma samples. Moreover, we observed that higher expression levels of DLGAP1-AS1 were correlated to shorter OS time in both low-grade and high-grade gliomas. Next, we evaluated the function of DLGAP1-AS1 in GBM using in vivo experiments. The data revealed that DLGAP1-AS1 knockdown greatly hindered U87 cell and U251 cell proliferation. Using coexpression network analysis, we identified that ATG4A was a potential downstream target of DLGAP1-AS1. The further analysis showed that ATG4B was significantly upregulated and correlated to shorter OS time in gliomas using both the CGGA and TCGA databases. Finally, we showed that ablated ATG4B greatly hindered GBM cell proliferation. Our conclusion suggested that DLGAP1-AS1 may be a potential prognosis biomarker and facilitated the occurrence and development of glioma via ATG4A in GBM.